2018
DOI: 10.1007/s10111-018-0527-6
|View full text |Cite
|
Sign up to set email alerts
|

Situation awareness based on eye movements in relation to the task environment

Abstract: The topic of situation awareness has received continuing interest over the last decades. Freeze-probe methods, such as the Situation Awareness Global Assessment Technique (SAGAT), are commonly employed for measuring situation awareness. The aim of this paper was to review validity issues of the SAGAT and examine whether eye movements are a promising alternative for measuring situation awareness. First, we outlined six problems of freeze-probe methods, such as the fact that freeze-probe methods rely on what the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 76 publications
4
44
1
Order By: Relevance
“…In some different studies, although no correlation between eye tracking metrics and direct SA measures was found, researchers offer that eye tracking metrics can be more beneficial in predicting performance in SA tasks compared with direct methods such as the SAGAT. For example, de Winter et al (2019) reported that the visual sampling score was found to be positively related to performance ratings, whereas In this study, the authors reported that "entropy" increased with CARS scores (p = .06). the correlation between the SAGAT score and performance rating was much less pronounced.…”
Section: Eye Tracking Measurescontrasting
confidence: 57%
“…In some different studies, although no correlation between eye tracking metrics and direct SA measures was found, researchers offer that eye tracking metrics can be more beneficial in predicting performance in SA tasks compared with direct methods such as the SAGAT. For example, de Winter et al (2019) reported that the visual sampling score was found to be positively related to performance ratings, whereas In this study, the authors reported that "entropy" increased with CARS scores (p = .06). the correlation between the SAGAT score and performance rating was much less pronounced.…”
Section: Eye Tracking Measurescontrasting
confidence: 57%
“…This analysis shows that claims that SAGAT is intrusive (Chiappe et al, 2012; de Winter et al, 2019; Durso et al, 1998; Salmon et al, 2011; Sarter & Woods, 1991) are unwarranted, with no negative effects on performance found in the 11 studies that examined it. The conditions of SAGAT administration are significantly different than interruptions with unrelated tasks.…”
Section: Discussionmentioning
confidence: 88%
“…Some researchers have examined the processes that people use to develop SA using measures such as eye tracking (de Winter, Eisma, Cabrall, Hancock, & Stanton, 2019; Ikuma, Harvey, Taylor, & Handal, 2014; Smolensky, 1993), communications (Bolstad et al, 2007; Gorman, Cooke, Pederson, Connor, & DeJoode, 2005; Orasanu, 2000; Prince, Salas, & Stout, 1995), verbal protocols (Hall & Phelps, 1983; Rose, Bearman, Naweed, & Dorrian, 2019; Sullivan & Blackman, 1991; Walker, Stanton, & Young, 2008), and physiological measurement (Wilson, 2000). While process measures can provide insights into how people develop SA, they can only be used to indirectly infer the quality and completeness of the resulting SA, as a state of knowledge about the situation, obtained by the individuals involved.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that pedestrians are inclined to look at the wheels of cars appears to be a novel finding in the literature. Exceptions are Aupetit, Espié, and Bouaziz (2015), who noted that motorcyclists look at the front wheels of cars to infer their intended lateral movement, and Vlakveld (2014; see also De Winter, Eisma, Cabrall, Hancock, & Stanton, 2019), who used turned front wheels as a hazard precursor in a hazard perception study.…”
Section: Accepted Manuscriptmentioning
confidence: 99%